Implementation of The Independent Learning - Independent Campus Policy at Universitas Negeri Manado - Talumewo, Victory; Tumbel, Goinpeace; Tarore, Steven (Technium Social Sciences Journal, 2023)
The objective of the Independent Learning - Independent Campus (MBKM) policy is to improve the competence of graduates, both soft skills and hard skills, so that they are more prepared and relevant to the needs of the times, preparing graduates as future leaders of the nation who are superior and have good personalities. The aims of this research are to 1) describe, analyze and interpret the implementation of the MBKM policy at Universitas Negeri Manado; 2) Describe, analyze and interpret the inhibiting and supporting factors for the implementation of MBKM policies at Universitas Negeri Manado. This research was conducted using a qualitative approach. The research location is Universitas Negeri Manado. Data collection techniques used are observation, interviews and document studies. The results of the study show that 1) Student Exchange Activities through MBKM have been carried out at Universitas Negeri Manado since 2020. However, only a few students at Universitas Negeri Manado have participated in the MBKM program, not all of them due to limited funds; 2) Many students from the Faculty of Engineering have participated in the MBKM Internship activities. The implementation of the MBKM Internship/Work Practice Activities has problems because the MBKM program is government-based and lecture in nature, in fact it can only be attended by students in semesters V and III; 3) The inhibiting factor in this MBKM policy is that the program is still new so it must be fully studied or it is still in the process of being developed. However, there are supporting factors for the MBKM policy, namely having many benefits for students and there are even awards given to students, namely giving a reward of 20 credits for all courses that have been determined by the study program.